Video Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) Murid Sekolah Dasar - Sumihardi; Erick Zicof; Adriyeni; Novelasari (CV. CENDIKIA JENIUS INDONESIA, 2026)
Clean and Healthy Living Behavior (PHBS) in schools is an essential strategy for preventing various diseases among school-age children. This community service program aimed to improve elementary school students' knowledge of PHBS through educational video media. The activity was conducted from July to October 2025 in five elementary schools within the working area of Bungus Teluk Kabung Primary Health Center, involving 300 students from grades IV, V, and VI. The implementation methods included educational video presentations, banner-assisted health education, discussions, simulations, and evaluation through post-tests and field observations. The results showed that 89.67% of the students achieved a good level of knowledge after participating in the educational program. Among the eight PHBS indicators, the highest level of knowledge was found in proper handwashing with soap and running water (94.67%), while the lowest was in mosquito larvae eradication (45.00%). Educational videos proved to be an effective health promotion medium by providing engaging, interactive, and easily understandable learning materials. In conclusion, educational videos effectively improve elementary school students' knowledge of PHBS and should be integrated into regular School Health Unit (UKS) activities to strengthen the sustainable implementation of healthy behaviors in schools.